Relevancy of Law No. 10 Year 2009 about Tourism Towards Creative Economy as a New Platform Of Tourism Development in Indonesia - Atsmara, Akiko Nada; Kusuma, Bayu Mitra Adhyatma (Journal of Indonesian Tourism and Development Studies, 2014)
It is necessary for human beings to become as creative as possible in order to maintain their viability. It can be said that human creativity emerges ever since the existence of humans on planet earth itself. Since year 2011 until now, Indonesia is the only country in the world having a big institution that uses the term creative economy that is the Ministry of Tourism and Creative Economy, formerly known as Ministry of Culture and Tourism. The emergence of the term Creative Economy itself hints that within the tourism development in Indonesia, the government is seeking to optimize creative economy sector, besides the country's natural and cultural heritage. On the other hand, up until now Indonesia still uses the Law No. 10 Year 2009 about Tourism as a platform in Indonesia's tourism development. This matter of course brings up challenges about several issues such as why does the government of Indonesia emphasizes on creative economy in their tourism development and is Law No. 10 Year 2009 about Tourism still relevant towards the development of creative economy in Indonesia. This research is based on a qualitative type, descriptive approach, and emphasize on the literature study. Keywords: Law No. 10 Year 2009, Creative Economy, Tourism Development